EMBEDDED GUIDE FOR THE BLIND - "PARTHIBAN , PRABU K R AND SHYJU K"; Mr.C.THIRUVENKATESAN ECE 105
"TRANSMISSION OF AN ULTRASONIC PULSE AND CALCULATION OF THE TIME. RS232 COMMUNICATION PROTOCOL,PSoC AND PRE RECORDED CHIP"
SOFT
UG